Penilaian Risiko Postur Kerja Berdasarkan Metode RULA Pada Pekerja Manual Handling di Toko H. Dadang - Mochamad Rafi Herdiana; Asep Erik Nugraha (Jurnal Serambi Engineering, 2023)
Manual material handling is a very important study in the industrial world. Conceptually, material handling in workers by utilizing labor. Flexibility of movement and wide accessibility are among the reasons the industry still utilizes manual material refining. On the other hand, the risk caused by the work is spinal injury (low back pain). Many use methods to analyze working postural on MMH. The study used the RULA method and a nordic body map questionnaire. The use of NBM questionnaires to find out complaints ergonomically, while the RULA Method is to analyze ergonomic risks in the upper part of the body. Toko H. Dadang is a grocery store that sells various basic necessities and others, with operators totaling 4 people. In the results of this study 4 people had upper ergonomic injuries. with the help of NBM questionnaires and analyzing the relationship of ergonomic risk with the RULA method. In the RULA method assesses the work of operators, on operators 1 it is worth 7. Thus, recommendations are given by using a freight trolley to prevent further ergonomic risks.